Temporary migration of Romanian Roma people to European countries - Meseşan-Schmitz, Luiza; Coman, Claudiu; Bódi, Diana-Cristina; Gotea, Mihaela (Frontiers in Sociology, 2025)
IntroductionRoma people in Europe are still in a great risk of social exclusion because of the stereotypes, prejudices, and discrimination against them, known as Antigypsyism. They also encounter high levels of poverty, lower levels of education, housing conditions, and health care, high rates of unemployment, and so on. Based on the push-pull theory, the present study examines the phenomenon of international migration of the Roma population from Olt County, Romania, capturing the specific factors that led to their migration and return to the country, and also the effects of this phenomenon on the community at the place of origin.Methodsour study used a mixed-methods approach, applying a non-standardized questionnaire to 796 Roma people who have experienced international, temporary migration and currently live in Olt County from Romania and semistructured interviews with 15 managers and representatives of the local public and socio-cultural institutions from the same region.Resultsthe results show us that the main push-pull factors of external migration of Roma people from Romania, as well as of their return home are economic and socio-cultural ones. Our data can add to the mentioned theory new pull factors for migration to certain countries, such as the friendly climate and easier learning of the language of the host country. We have also discovered that family is the main factor for returning home to Romania, and also the disappointment of their migration experience. The effects of their return migration on them and the community can be positive (e.g., cultural exchange, awareness of the role of education), but also negative (e.g., increasing unemployment, the negative image of Romania).Conclusionthe findings highlight some assumptions of the push-pull theory, but they also bring new perspectives for understanding and approaching this phenomenon. The perspectives of Roma and representatives of institutions are different regarding the push factors that generate external migration of Roma, Roma identify only economic factors that lead to migration, while managers and representatives also talk about socio-cultural factors involved in the decision to migrate of Roma. The study also identifies the implications generated by the return home of the Roma, with economic, socio-cultural, and educational effects, but also effects at the level of public policies. We believe that the push-pull factors of external migration and the effects of Roma's return to the country are interconnected, generating an amplification of the problems for which Roma migrate. Therefore, they constitute solid arguments for building and streamlining social integration policies for Roma.